EFFECT OF PROFITABILITY ON FIRM VALUES WITH MANAGERIAL OWNERSHIP AS A VARIABLE CONTROL - Wahju Widajatun, Vincentia (International Journal of Psychosocial Rehabilitation, 2020)
Corporate perception of the value of the company. Firm value can be measured by the state of the company’s stock price in the market. Reflections on evaluations by the public on the performance of companies in real terms create the creation of company stock prices in the market. Measurement of firm value can be done with several calculations, one of which is the Tobin’s Q ratio. In the past 5 years, the value of the construction and building sub-sector companies has continued to decline. This study aims to analyze the effect of profitability on firm value in the presence of managerial ownership control variables in the construction and building sub-sector companies in the 2014-2018 period. ROE has a significant effect on firm value. With the managerial ownership control variable, there is an increase in the coefficient of determination.